Restriction of Mouth Opening, Reduction in Pressure Pain Thresholds and Activation of Myofascial Trigger Points in Mandibular and Cervical Regions after Root Canal Therapy: A Quasi-Experimental Study - Isabel Albarova-Corral; Óscar Alonso-Ezpeleta; Santiago Poc-Sola; Silvia Cardiel-Sánchez; Andoni Carrasco-Uribarren; Miguel Malo-Urriés (Applied Sciences, 2023)
Background: In daily clinical practice, patients often refer temporomandibular or cervical complaints after different oral procedures, especially in lengthy procedures that can result in iatrogenic postures or trauma that can affect the temporomandibular joint (TMJ). This study aimed to evaluate the clinical and functional changes of the temporomandibular joint (TMJ) and cervical region immediately after a session of root canal therapy. Methods: Twenty-nine subjects who received a session of root canal therapy were included. Clinical assessments included mouth opening, cervical mobility, pain intensity, pressure pain thresholds (PPTs), and myofascial trigger points (MTrPs) of the jaw and neck muscles. Results: After the intervention, a significant reduction in mouth opening (41.90 mm; SD = 6.21) was observed compared to baseline (46.28 mm; SD = 6.17) (p < 0.001). A significant reduction in PPTs and cervical mobility (p < 0.05), and an increase in MTrPs (p = 0.002–0.026) were demonstrated after the intervention. Conclusions: A session of root canal therapy can produce an immediate significant reduction in mouth opening, PPTs, and cervical mobility, and an increase in MTrPs. The risk can be higher if there is a previous TMJ limitation.